If You're Reading This, It's Too Late - Bosch, Pseudonymous; Ford, Gilbert (New York : Little, Brown, 2008)
Cass and Max-Ernest discover the Museum of Magic, unscramble more coded messages, and solve new mysteries in their attempt to thwart the Terces Society's ambitions of discovering immortality.
Sequel to: The name of this book is secret.
008-012.
Keywords: Magic tricks -- Fiction; Fiction; Immortality -- Fiction